The Influence of Service Quality on Consumer satisfaction Delivery Services at JNT Express in Garut - Nurul Fauziyah Rahmah; Fitriani Nur Utami (Budapest International Research and Critics University, 2022)
The development of commerce is one of the many factors that drive the development of logistics in Indonesia. The reason for this to happen is due to the large demand for goods delivery services. JNT Express is one of the 2nd most popular shipping services in Indonesia which has a good existence and achievements. Because JNT Express is the most frequently used delivery service, in fact many consumer complaints arise due to the poor implementation of service quality and its impact on customer satisfaction. The high use of delivery services and similar online shop makes delivery services need to pay attention to and improve service quality so that there are no complaints about services so that they get satisfaction and a positive experience in the eyes of consumers. In this research, the aim is to obtain information on